Metodologia para otimização em subcontratação de serviço de usinagem - Pinto, Anderson Rogério Faia [UNESP] (2013)
Operational Research (OR) is an eminent science to business competitiveness and the capacity of algorithms and spreadsheets that exist today allows people to apply them for a lower cost and with less complexity. However, spreadsheets linked to OR techniques, when directed to real problems, are still little explored in their full potential. In order to use them better, this article utilizes the Microsoft Office Excel to solve an optimization practical problem and decision-making of machining subcontracting. In general, although considered a frequent problem, is not of easy solution, optimize the mix of production versus outsourcing, because of the restrictions and resources available, it requests investments in specific software. In this way, this research aims to develop software to be called SOSU (Optimization Software for Machining Subcontracting). SOSU should introduce the best mix of internal and subcontracted machining for n types of parts that, over a certain period of time t, maximize capacity and meet all the demand at the lowest cost possible. The methodology adopted follows the bibliographic reference and it is assumed that the necessary data to prove from mathematical modeling of production areas and from a system of costs already structured. The nature of the problem justifies the application of Linear Programming (LP), Visual Basic for Applications (VBA) is used for computational implementation and interface with the user and the supplement Solver to find the solution. The analysis of the experiments show that the SOSU optimizes resources and improves the decision-making process, besides an easy operation, it can be implemented or quickly adapted and without the need of large investments.